Distribution and determinants of patient satisfaction in oncology with a focus on health related quality of life - Gupta Digant; Grutsch James F; Rodeghier Mark; Lis Christopher G (BMC, 2009)
Abstract Background Cancer patients usually undergo extensive and debilitating treatments, which make quality of life (QoL) and patient satisfaction important health care assessment measures. However, very few studies have evaluated the relationship between QoL and patient satisfaction in oncology. We investigated the clinical, demographic and QoL factors associated with patient satisfaction in a large heterogeneous sample of cancer patients. Methods A cohort of 538 cancer patients treated at Cancer Treatment Centers of America® (CTCA) was assessed. A patient satisfaction questionnaire developed in-house by CTCA was used. It covered the following dimensions of patient satisfaction: hospital operations and services, physicians and staff, and patient endorsements for themselves and others. QoL was assessed using the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (QLQ-C30). The clinical, demographic and QoL factors were evaluated for predictive significance using univariate and multivariate logistic regression. Results The mean age of our patient population was 54.1 years (SD = 10.5, range 17-86), with a slight preponderance of females (57.2%). Breast cancer (n = 124) and lung cancer (n = 101) were the most frequent cancer types. 481 (89.4%) patients were "very satisfied" with their overall experience. Age and several QoL function and symptom scales were predictive of overall patient satisfaction upon univariate analysis. In the multivariate modeling, only those with a score above the median on the fatigue measure (i.e. worse fatigue) had reduced odds of 0.28 of being very satisfied (p = 0.03). Conclusion Patient fatigue, as reported by the QoL fatigue scale, was an independent significant predictor of overall patient satisfaction. This finding argues for special attention and programs for cancer patients who report higher levels of fatigue given that fatigue is the most frequently reported symptom in cancer patients.